Reforming the Liturgy : A Response to the Critics - Baldovin, John F. (John Francis), 1947- (Book collections on Project MUSE., 2008)
"In this summary volume on the reform of the liturgy since the Second Vatican Council, Baldovin pinpoints and assesses - both sympathetically and critically - the objections to changes in the liturgy since the council, focusing on philosophical, historical-critical, and theological questions. After addressing each criticism in turn, in a final chapter he assesses the critique of post-Vatican II liturgy as a whole, affirming what is accurate and necessary, rejecting what is backward looking, and proposing a set of principles to guide future development. No one who studies or participates in liturgical action in the twenty-first century can afford to overlook this book."--BOOK JACKET.